2021
DOI: 10.1089/jpm.2020.0311
|View full text |Cite
|
Sign up to set email alerts
|

Models of Palliative Care Delivery for Individuals with Cystic Fibrosis: Cystic Fibrosis Foundation Evidence-Informed Consensus Guidelines

Abstract: Cystic fibrosis (CF) affects more than 70,000 individuals and their families worldwide. Although outcomes for individuals with CF continue to improve, it remains a life-limiting condition with no cure. Individuals with CF manage extensive symptom and treatment burdens and face complex medical decisions throughout the illness course. Although palliative care has been shown to reduce suffering by alleviating illness-related burdens for people with serious illness and their families, little is known regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…The strongest evidence for palliative care is its association with improved QoL and reduced symptom burden. 1 The Functional Assessment of Chronic Illness Therapy-Palliative care (FACIT-Pal), a disease-generic measure, will be used to assess the primary study outcome, patient-reported QoL. 2 FACIT-Pal is a 46-item measure that evaluates overall QoL (27 items) and contains a palliative subscale measuring factors particularly salient to individuals living with serious illness (19 items).…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest evidence for palliative care is its association with improved QoL and reduced symptom burden. 1 The Functional Assessment of Chronic Illness Therapy-Palliative care (FACIT-Pal), a disease-generic measure, will be used to assess the primary study outcome, patient-reported QoL. 2 FACIT-Pal is a 46-item measure that evaluates overall QoL (27 items) and contains a palliative subscale measuring factors particularly salient to individuals living with serious illness (19 items).…”
Section: Methods and Analysismentioning
confidence: 99%
“…People living with cystic fibrosis (CF) and their caregivers experience multidimensional suffering and impaired quality of life (QoL). 1 2 CF is a progressive, multisystem genetic disease occurring in an estimated >160 000 people worldwide. 3 4 Therapeutic advances, including cystic fibrosis transmembrane conductance regulator (CFTR) modulators, have increased life expectancy and lung function in CF, yet people with CF continue to experience high physical symptom burden (eg, dyspnoea, fatigue, pain) and emotional distress (eg, depression, anxiety), both of which significantly impair functional status and QoL.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent 2020 study, a group of over 500 individuals, including people with cystic fibrosis, their caregivers, and their medical teams identified multiple key palliative care needs, including assistance with the complexity of treatment regimens, emotional support, mental health management, and guidance through shared decision making with advanced care planning [10]. In order to better identify these needs on an individual level, the CFF also recommends administering the standardized Integrative Palliative Care Outcome Scale starting at age 12, annually, and with disease milestones such as changes in severity or functional decline [11].…”
Section: Palliative Care In Cystic Fibrosismentioning
confidence: 99%
“…It is, therefore, unsurprising that the prevalence of these comorbidities is higher in individuals with cystic fibrosis (9-46%) and their caregivers (20-35%) compared to the general population [15]. These high rates of anxiety and depression underscore the importance of screening in both groups, with the Patient Health Questionnaire 9 Item Scale (PHQ-9) and Generalized Anxiety Disorder 7 Item Scale (GAD-7) offering quick, validated options for recommended annual assessment [11]. Appropriate management of mental health has clear consequences on illness progression, as anxiety and depression have been strongly associated with both treatment adherence and health-related quality of life [16,17].…”
Section: Palliative Care In Cystic Fibrosismentioning
confidence: 99%
See 1 more Smart Citation